Clinical and Economic Efficiency of Vaccination in a Pneumococcal 13-Valent Conjugate Vaccine in Patients with Chronic Bronchitis at a Young Age - G. L. Ignatova; I. A. Zakharova; V. N. Antonov (Эпидемиология и вакцинопрофилактика, 2017)
The high prevalence of chronic bronchitis (CB) among young people, and significant pharmaco-economic costs of health care for treatment of this disease actualizes the search for new solutions for the prevention of exacerbations. The goal is to prove the clinical and economic efficacy of vaccination in a pneumococcal 13-valent conjugate vaccine for the prevention of exacerbations of chronic bronchitis in persons of young age. Materials and methods. It was compared 2 groups: vaccinated with the use of pneumococcal 13-valent conjugate vaccine (n = 57), and not vaccinated against pneumococcal infection (n = 129). Endpoints were: number of exacerbations of chronic bronchitis, including the number of outpatient and inpatient cases, the number of pneumonias per year. Statistical processing of the obtained material was carried out using PPP - Statistica 12. The results and discussion. In the group of the 129 of patients who have not received PCV13 vaccination, marked by the 25.5% of the episodes of exacerbations of CB, whereas in the vaccinated group was observed 8.8% of episodes of exacerbations of CB, and no cases of pneumonia (RR = 0.32; 95% CI: 0.13 - 0,78; p < 0.05). Under the annual horizon of the study, the total direct and indirect costs associated with the disease HB in both groups were not significantly different, amounting to rub 2 661.8, and 3395.4 rub per patient with and without vaccination, respectively. In the three-year horizon of the study, reducing outpatient and inpatient episodes of treatment of acute exacerbations of chronic bronchitis will reduce the total economic damage from the disease to 28%. Conclusion. The results obtained demonstrate significant clinical efficacy of vaccination with the use of PCV13 in reducing the number of exacerbations in 2.7 times and high economic efficiency leads to higher costs in the year of vaccination and allow them to forecast substantial savings in subsequent years, reaching 35.1 и 48.3% after 2 and 3 years after vaccination.